University proceedings. Volga region. Natural sciences - O.N. Kurdyukova; Yu.G. Zarutskaya (Известия высших учебных заведений. Поволжский регион: Естественные науки)
Background. In urban green construction of Lugansk, the selection of fast-growing trees and shrubs with a high decorative effect is important. The purpose of the study is to establish the species composition, bioecological characteristics and decorative qualities of species of the Populus L. suitable for landscaping. Materials and methods. Floristic surveys were carried out during March-November, in squares measuring 1×1 km. Dendrological and biometric records, observations and descriptions were carried out according to the methods of the Nikitsky Botanical Garden. Results. In the green spaces in Lugansk there were 9 taxon of the genus Populus L. – Populus alba L., Populus alba var. bolleana (Lauche) Ed. Otto, Populus tremula L., Populus deltoides W. Bartram ex Marshall, Populus nigra L., Populus nigra var. italica (Moench) Koehne), Populus simonii Carrière, Populus × berolinensis K. Koch, Populus × canadensis Moench. In the conditions of Lugansk, these are dioecious, dioecious, deciduous, anemophilously pollinated, intensively growing, tall trees that retain intense leaf color throughout the growing season, and in the fall – a rich range of colors, but differ in different resistance to natural environmental and anthropogenic influences and unequal decorative advantages. Conclusions. All taxon Populus L. can withstand the conditions of an urban and industrial environment well, are characterized by intensive growth, relatively low demands on soil fertility, sufficient drought resistance, winter hardiness, are highly decorative and rightfully occupy a leading place in the green spaces of the city.